Deficient host-bacteria interactions in inflammatory bowel disease? The toll-like receptor (TLR)-4 Asp299gly polymorphism is associated with Crohn's disease and ulcerative colitis. Issue 7 (11th June 2004) - Franchimont, D; Vermeire, S; El Housni, H; Pierik, M; Van Steen, K; Gustot, T; Quertinmont, E; Abramowicz, M; Van Gossum, A; Devière, J; Rutgeerts, P
Abstract : Background and aims: Elicitation of an innate immune response to bacterial products is mediated through pattern recognition receptors (PRRs) such as the toll-like receptors (TLRs) and the NODs. The recently characterised Asp299Gly polymorphism in the lipopolysaccharide (LPS) receptor TLR4 is associated with impaired LPS signalling and increased susceptibility to Gram negative infections. We sought to determine whether this polymorphism was associated with Crohn's disease (CD) and/or ulcerative colitis (UC). Methods: Allele frequencies of the TLR4 Asp299Gly polymorphism and the three NOD2/CARD15 polymorphisms (Arg702Trp, Gly908Arg, and Leu1007fsinsC) were assessed in two independent cohorts of CD patients (cohort 1, n = 334; cohort 2, n = 114), in 163 UC patients, and in 140 controls. A transmission disequilibrium test (TDT) was then performed on 318 inflammatory bowel disease (IBD) trios. Results: The allele frequency of the TLR4 Asp299Gly polymorphism was significantly higher in CD (cohort 1: 11% v 5%, odds ratio (OR) 2.31 (95% confidence interval (CI) 1.28–4.17), p = 0.004; and cohort 2: 12% v 5%, OR 2.45 (95% CI 1.24–4.81), p = 0.007) and UC patients (10% v 5%, OR 2.05 (95% CI 1.07–3.93), p = 0.027) compared with the control population. A TDT on 318 IBD trios demonstrated preferential transmission of the TLR4 Asp299Gly polymorphism from heterozygous parents to affected children (T/U: 68/34, p = 0.01). Carrying polymorphisms in both TLR4 and NOD2 was associated with a genotype relative risk (RR) of 4.7 compared with a RR of 2.6 and 2.5 for TLR4 and NOD2 variants separately. Conclusion: We have reported on a novel association of the TLR4 Asp299Gly polymorphism with both CD and UC. This finding further supports the genetic influence of PRRs in triggering IBD.